2020
DOI: 10.1177/0300060520918407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane and propofol anesthesia on intraoperative endothelial cell function in patients undergoing laparoscopic cholecystectomy

Abstract: Objectives To investigate the effects of sevoflurane and propofol anesthesia on inflammatory or anti-inflammatory responses in patients undergoing laparoscopic cholecystectomy (LC). Methods Patients undergoing LC (n = 23) were divided into sevoflurane (S) (n = 11) and propofol (P) (n = 12) anesthesia groups. A blood sample was taken before induction (T0), after induction but before pneumoperitoneum (T1), 15 minutes after pneumoperitoneum (T2), immediately after extubation (T3), and 30 minutes after extubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Endothelial cells, located within blood vessels, play a crucial role in maintaining normal vascular function and preventing inflammatory responses ( Figarola et al, 2014 ). Research indicates that propofol can reduce endothelial cell inflammatory reactions and damage, helping to preserve normal vascular function ( Fan et al, 2020 ).…”
Section: General Anesthetics and Auxiliary Drugs Regulate Peripheral ...mentioning
confidence: 99%
“…Endothelial cells, located within blood vessels, play a crucial role in maintaining normal vascular function and preventing inflammatory responses ( Figarola et al, 2014 ). Research indicates that propofol can reduce endothelial cell inflammatory reactions and damage, helping to preserve normal vascular function ( Fan et al, 2020 ).…”
Section: General Anesthetics and Auxiliary Drugs Regulate Peripheral ...mentioning
confidence: 99%
“…Propofol (Pro), an intravenous anesthetic, is generally used for the sedation of surgical patients [14,15]. Remarkably, Pro administration has shown to attenuate organ I/R injury and improve surgical outcomes in clinical and preclinical settings [11,[16][17][18].…”
Section: Agingmentioning
confidence: 99%
“…6 Furthermore, increasing evidence has shown that sevoflurane and propofol have antiinflammatory effects. [7][8][9][10] ARDS refers to an acute inflammatory response associated with diffuse lung infiltrates resulting in a systemic inflammatory response syndrome (SIRS). 11 Apart from lung disease, VV ECMO is also initiated in instances of rapid and complex inflammatory response, similar to that seen in SIRS.…”
Section: Introductionmentioning
confidence: 99%